Inassimiláveis ou prejudicialmente assimiláveis ? Raça, etnia, miscigenação, imigração e trabalho na perspectiva de Fidélis Reis (1919-1934) - Riccioppo, Thiago (2014)
In this research work, we aimed to compile the speeches uttered and/or made by the politician from Uberaba, Fidélis Gonçalves dos Reis, also known as Fidélis Reis (1880-1962), as well as the texts about him or collected by him - speeches, political projects, letters, memoranda, press articles, publications by his authorship and by other authors, with the intent to track his reflections about some main themes and problems which were targets not only of his concerns, but also of the political debate on the country, such as the economy, laboring, immigration, the population and the destiny of the Brazilian nation. The documents were gathered for being frequent subjects in the historical sources, highlighted and underlined repeatedly in different moments of the politician‟s trajectory, in his actions and articulations in the legislative scope and even in his daily actions like his memorial writings. The material contains representations and meanings which represent not only the object of his concerns but also his public and private relations, as well as his sociability webs that were settling down around the years of 1919 to 1934, thus drawing the outlines of a group of political themes. During the reading and the analysis for this research, it was possible to be in touch with the praising and the depreciative images of the nation and the efforts to formulate a perspective in which we can find common-places and common-backgrounds about the ethnic concepts, the enhancement of the races and the constitution of a Brazilian national identity. The research resulted in a reconstruction of an itinerary with which we proposed a reflection about some of the conflicts and the issues faced by his generation in the extent of the country‟s political culture during that historical period of time.